Mulheres, endividamento e feminização da pobreza: a urgência de políticas públicas de gênero para a transformação dessa realidade no Brasil entre 2015 e 2025 - Agapito, Aline Silva (2024)
The dissertation analyzes the situation of women's indebtedness and the feminization of poverty in Brazil, addressing the structural inequalities that perpetuate this reality and the need for specific public policies to mitigate its effects. The study uses a qualitative approach, based on a bibliographic survey and analysis of official data, with the aim of deepening the understanding of structural inequalities in the labor market, addressing the gaps in studies of external public policies for women in single-parent homes. In addition, the research presents official data on the labor market and women's indebtedness and analyzes existing government actions to transform practices aimed at this group. The main sources of this data are the Brazilian Institute of Geography and Statistics (IBGE) and the National Confederation of Trade in Goods (CNC). It is noteworthy that the financial burden of these women is exacerbated by precarious conditions in the labor market, marked by high informality and wage disparities. The work also considers how behavioral economics can offer valuable insights to understand the financial decision-making patterns of these women, often influenced by time constraints, resources, and stress, contributing to the perpetuation of indebtedness. The research presents evidence that effective public policies that integrate intersectional gender and race perspectives have the potential to reduce debt levels and promote greater economic stability. It concludes that the implementation of targeted, specific and restricted measures to encourage women's financial and social independence is essential to break the cycle of poverty and foster greater equity in access to economic and social opportunities.